2018
DOI: 10.3389/fphar.2018.00500
|View full text |Cite
|
Sign up to set email alerts
|

Kinin and Purine Signaling Contributes to Neuroblastoma Metastasis

Abstract: Bone marrow metastasis occurs in approximately 350,000 patients that annually die in the U.S. alone. In view of the importance of tumor cell migration into the bone marrow, we have here investigated effects of various concentrations of stromal cell-derived factor-1 (SDF-1), bradykinin- and ATP on bone marrow metastasis. We show for first time that bradykinin augmented chemotactic responsiveness of neuroblastoma cells to SDF-1 and ATP concentrations, encountered under physiological conditions. Bradykinin upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 44 publications
(54 reference statements)
3
45
1
Order By: Relevance
“…Adinolfi and colleagues first demonstrated the growth-promoting activity of P2X7 in four different tumor models in mice including HEK-293 cells and ACN neuroblastoma derived xenografts and syngeneic colon carcinoma and melanoma models (Adinolfi et al, 2012a). Several studies have confirmed these data and extended them, demonstrating that P2X7 blockade leads to a general reduction of tumor burden in neuroblastoma (Amoroso et al, 2015;Ulrich et al, 2018), mesothelioma (Amoroso et al, 2016), melanoma Adinolfi et al, 2015a), glioma (Ji et al, 2018), osteosarcoma (Zhang et al, 2019a) and myeloid leukemia (De Marchi et al, 2019a).…”
Section: Proliferationmentioning
confidence: 99%
“…Adinolfi and colleagues first demonstrated the growth-promoting activity of P2X7 in four different tumor models in mice including HEK-293 cells and ACN neuroblastoma derived xenografts and syngeneic colon carcinoma and melanoma models (Adinolfi et al, 2012a). Several studies have confirmed these data and extended them, demonstrating that P2X7 blockade leads to a general reduction of tumor burden in neuroblastoma (Amoroso et al, 2015;Ulrich et al, 2018), mesothelioma (Amoroso et al, 2016), melanoma Adinolfi et al, 2015a), glioma (Ji et al, 2018), osteosarcoma (Zhang et al, 2019a) and myeloid leukemia (De Marchi et al, 2019a).…”
Section: Proliferationmentioning
confidence: 99%
“…Consistently, overexpression of the P2X7 receptor in a naturally low-expressing human glioma cell line conferred modest in vitro growth advantages, but largely accelerated tumor growth in vivo (Bergamin et al, 2019), reinforcing a trophic role for this receptor. Also, in a mouse model of neuroblastoma, a rare intracranial tumor that affects immature or developing cells of the nervous system, chronic blockade of the P2X7 receptor in tumor-bearing mice diminished progression and metastasis (Ulrich et al, 2018).…”
Section: Brain Tumorsmentioning
confidence: 99%
“…A pathophysiological role of P2X7R-B has been described in multiple conditions, including bone cancer ( Giuliani et al, 2014 ) and bone differentiation ( Carluccio et al, 2019 ). It has also been described in neural progenitors ( Glaser et al, 2014 ), neuroblastoma cells ( Ulrich et al, 2018 ), and glioblastoma cells ( Ziberi et al, 2019 ). P2X7R-H contains 505 aa and is also known as P2X7R-ΔTM1, since the TM1 is absent.…”
Section: Introductionmentioning
confidence: 99%